Pd doping-weakened intermediate adsorption to promote electrocatalytic nitrate reduction on TiO2 nanoarrays for ammonia production and energy supply with zinc–nitrate batteries. Issue 7 (22nd June 2021) - Guo, Ying; Zhang, Rong; Zhang, Shaoce; Zhao, Yuwei; Yang, Qi; Huang, Zhaodong; Dong, Binbin; Zhi, Chunyi
Abstract : An electrochemical nitrate-based cell enables both ammonia production and energy supply. Abstract : The (photo)electrochemical nitrogen reduction reaction for ammonia (NH3 ) production is an appealing alternative to the traditional high-energy Haber–Bosch reaction. However, the future of this approach is bleak because of the ultralow N2 solubility and the nonpolar NN bond causing the NH3 yield and selectivity to be unsatisfactory. Nitrate electroreduction (NORR) into NH3 brings promise for the future landscape of NH3 electrosynthesis due to the low NO bond energy and high nitrate solubility. Here, we report a highly efficient Pd-doped TiO2 nanoarray electrode for NH3 production from the NORR. With weakened adsorption abilities to the intermediates induced by Pd introduction, the catalyst delivers a record-high NH3 yield of 1.12 mg cm −2 h −1 (or 0.066 mmol cm −2 h −1 ), an impressive NH3 faradaic efficiency (FE) of 92.1%, and an exceptional nitrate conversion of 99.6%. Considering an eight-electron nitrate-to-ammonia reaction and the excellent electrocatalytic activity of Pd/TiO2, we, for the first time, propose and develop a Zn–nitrate battery system, which delivers striking bifunctionality for harnessing the electrons related to the NORR to generate electricity and directly produce NH3, specified by a power density of 0.87 mW cm −2 and a high NH3 FE of 81.3%. Our work not only verifies the positive effect of Pd doping on facilitating the NORR, but also demonstrates a galvanic nitrate-based cell providing a promising strategy for NH3 production and broadening the field of Zn-based batteries.